The influence of a program of education in men health - Fernandes Leite, Denise; Gonçalves Ferreira, Iracema Maria; de Souza, Marta Solange; Silva Nunes, Vanessa; de Castro, Paulo Roberto (O Mundo da Saúde, 2010)
The objective of this study was to give male individuals knowledge on global aspects of health and verify if the program of education in health brought benefits and changes to their lives. It is a prospective study with a quail-quantitative approach. Six lectures in two companies had been carried through, with the participation of 25 male collaborators. In the first one and the last meeting, we applied the same questionnaire with 15 multiple choice questions. In a second moment, an open question was added whose answers were analyzed under the perspective of the Collective Subject Discourse (DSC). The research was approved by the Committee of Ethics in Research (process n.60/08). The age of subjects was 18 to 49 years; 36% had completed secondary education. We observed that in relation to health and life habits, the intervention of the lectures had not produced significant changes. However, the level of knowledge about hypertension, diabetes, prostate cancer and vascular-encephalic accidents presented a significant improvement. One concluded that the strategy of education in health of men had a positive impact in the knowledge on the diseases. DSC analysis showed a greater awareness on the importance of prevention and the adoption of a healthful life habit. This shows to be necessary more actions directed to this group, which is not adequately contemplated by the public health policies, as proves the literature.